A Comparative Analysis of Uzbek and English Grammar: Exploring Notional Parts of Speech - Zokirova Malikaxon Ğulomjon qizi, Muhammadiyev Aziz Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article aims to provide a comparative analysis of the grammatical structure of Uzbek and English, with a particular focus on notional parts of speech. By examining the similarities and differences in the categorization and usage of these parts of speech in both languages, we aim to shed light on the unique features of each language and improve our understanding of cross-linguistic variations in grammar. The analysis is based on a comprehensive review of relevant literature, including linguistic studies and grammatical descriptions of Uzbek and English.